The effects of growing up on a farm on adult lung function and allergic phenotypes: an international population-based study. Issue 3 (26th September 2016) - Campbell, B; Raherison, C; Lodge, C J; Lowe, A J; Gislason, T; Heinrich, J; Sunyer, J; Gómez Real, F; Norbäck, D; Matheson, M C; Wjst, M; Dratva, J; et al.
Abstract : Rationale: Evidence has suggested that exposure to environmental or microbial biodiversity in early life may impact subsequent lung function and allergic disease risk. Objectives: To investigate the influence of childhood living environment and biodiversity indicators on atopy, asthma and lung function in adulthood. Methods and measurements: The European Community Respiratory Health Survey II investigated ∼10 201 participants aged 26–54 years from 14 countries, including participants' place of upbringing (farm, rural environment or inner city) before age 5 years. A 'biodiversity score' was created based on childhood exposure to cats, dogs, day care, bedroom sharing and older siblings. Associations with lung function, bronchial hyper-responsiveness (BHR), allergic sensitisation, asthma and rhinitis were analysed. Main results: As compared with a city upbringing, those with early-life farm exposure had less atopic sensitisation (adjusted OR 0.46, 95% CI 0.37 to 0.58), atopic BHR (0.54 (0.35 to 0.83)), atopic asthma (0.47 (0.28 to 0.81)) and atopic rhinitis (0.43 (0.32 to 0.57)), but not non-atopic outcomes. Less pronounced protective effects were observed for rural environment exposures. Women with a farm upbringing had higher FEV1 (adjusted difference 110 mL (64 to 157)), independent of sensitisation and asthma. In an inner city environment, a higher biodiversity score was related to less allergic sensitisation. Conclusions: This is the first study to report beneficial effects of growing up on a farm on adult FEV1 . Our study confirmed the beneficial effects of early farm life on sensitisation, asthma and rhinitis, and found a similar association for BHR. In persons with an urban upbringing, a higher biodiversity score predicted less allergic sensitisation, but to a lesser magnitude than a childhood farm environment.